Ergonomics analysis of gunner station of armoured combat vehicle (ACV)- Tank T 90S with special reference to seat, visual sighting system and musculoskeletal discomfort: A pilot study - Sinha, Pankaj Kumar; Pal, Madhusudan; Chandel, Sunil (Asian Journal of Medical Sciences, 2021)
Background: A combat vehicle is a tracked/wheeled land or amphibious vehicle, with or without armour or armament, designed for specific functions in combat or battle. It is an integrated mobile weapon platform comprising of multiple workstations having many equipment, switches, control and displays.Effectiveness of Combat vehicle and efficiency of crewin battle field depends upon the optimum design and placement of control and displays and workstation. Till date ergonomics studies on combat vehicle are limited and less reported. Aims and Objective: Present study was undertaken to investigate the gunner station of the combat vehicle (Tank T90 S) with special reference to seat and sighting system with respect to anthropometric dimensions of the crew members, to find out constraints, design limitations and mismatch in the existing vehicles; and the biomechanical responses (force and angles), comfort and discomfort during the vehicle operation. Materials and Methods: Ninety (90) healthy male gunner with mean age 35.2±8.5 years, stature 172.6±7.5 cm and weight 72.4±7.2 kg volunteered for the study. Anthropometric details of gunner crew, gunner seat dimension, sighting system, biomechanical response during operation, comfort and discomfort analysis were studied. Results: Gunner station sighting control handle is located below the recommended optimum vortex angle of ±15° from normal line of sight in vertical and horizontal plane. Hand grip strength decreased with increasing operation time. Reduction in grip strength of the gunner may tend to produce lag and delay of movement of barrel and swiftness of gunner may get compromised. Seat was not designed as per anthropometric dimensions of crew members. Conclusion: Present study clearly stated that non-accessibility and difficulty in operating the handle of Gun Control Equipment during operation. Sighting system and seat of existing tank is poorly ergonomically designed. Hand grip strength gradually decrease with increasing operation time.